School-Based Mental Health Practice: The Impact of Physical Activity on Depression - Nafees Alam; Joy Krug (International Journal of School Social Work, 2025)
The relationship between physical and mental health has long been theorized to be profoundly important in understanding human behavior and development. This article aims specifically to highlight the state of existing research about the relationship between physical activity and the state of depression. Studies across the nation, summarized here, have found that healthy physical activity levels generally correlate with health within the mental and emotional arenas. Despite the abundance of existing literature on this topic, research remains scarce on the longitudinal effects of physical activity beginning with pre-puberty children into adulthood. Physical activity is a relatively cheap and non-harmful lifestyle intervention that school-based mental health practitioners can quickly implement in school settings. School social workers aligned with evidence based practice could stay current on advancing literature in this arena to learn what research has gleaned and apply that research within school settings. School social workers should also be encouraged to publish innovative ways they’ve implemented physical activity in addressing student depression. This is an opportunity for school social workers across the globe to influence future generations to live healthier and happier lives positively.
Keywords: School-based mental health practice; Depression; Physical Activity; MDD